Diseño de la documentación del sistema de gestión de seguridad y salud en el trabajo para la empresa Unión Colombiana De Juegos S.A.S., con base en la resolución 0312 de 2019 (2023)
The work was based on the preparation and drafting of the design of the formats required by the SG-SST for the company Unión Colombiana de Juegos S.A.S., adopting the minimum standards for companies with 11 to 50 workers, according to Resolution 0312 of 2019, this with the objective, that the organization of order and compliance with the obligations and requirements of law.